Investigating the Critical Success Factors for Water Supply Projects: Case of Iraq - Al-Juboori Omar Akrm; Rashid Hatim A.; Mahjoob Ahmed Mohammed Raoof (Civil and Environmental Engineering, 2021)
Water supply projects (WSP) requires high plan information, specialized capabilities, capable human resources, and high administrative capacity. However, in the developing countries, particularly in Iraq, these projects experience a lack of a large number of these necessities, which shows the need to identify the critical success factors (CSFs). Accordingly, the objectives of this research are to investigate the CSFs for WSP and their significance among the construction (public and private) and education sectors. To achieve this, first we have carried out a comprehensive literature review of the CSFs for WSP. Second, we administrated a questionnaire survey to 260 construction experts working in the construction and education sectors. It was found that the top five important success factors for water supply projects in Iraq were a stable political environment; sustainable construction legislation and regulation; effective risk management practices; well-organized and committed project teams; and government decisions through the project life cycle. The survey results did not indicate major differences in the perception of the experts. The findings are focused to assist construction practitioners’ gain better understanding on the important areas to achieve project set objectives.